EP960 Total omentectomy versus omental sampling in early ovarian cancer surgery. (1st November 2019) - Refky, B; Gaballah, K; Attallah, K; Mohamed, H
Abstract : Introduction/Background: Historically the omentum was found to be a primary site of metastatic spread and invariably involved in all cases of advanced ovarian cancer, omentectomy was included for the staging and treatment of ovarian cancer regardless of whether or not the omentum appeared macroscopically to be involved. However, this dictum is not being routinely applied for the peritoneum, which is in the mainstay a common site for ovarian cancer metastastis and recurrence, only random peritoneal biopsies are obtained in early stage ovarian cancer, rarely total peritonectomy or removal of unaffected peritoneum is done Methodology: A prospective randomized controlled trial including 150 patients with early ovarian cancer for 5 years period in oncology center, Mansoura University, Egypt randomized in between two groups, Group 1 (control group) underwent conventional total infracolic omentectomy and the other group (Group 2) underwent just omental biopsy in apparently free omentum, just like peritoneal biopsies. Follow up to be done over a period of 5 years, however interim analysis was done after 2 years from the start of the trial. Results: In this interim analysis 89 patients were included, 46 underwent total omentectomy while 43 underwent omental biopsies only, out of those 43 patients three patients (6.9%) were found to have microscopic omental metastasis alone and thus were upstaged, however 2 years disease free survival was similar in both groups (93% in group 1 versus 91% in group 2). Conclusion: Total omentectomy may not be mandatory in the context of comprehensive surgical staging in early stage ovarian cancer, no difference was encountered regarding the disease free survival whether performing total omentectomy versus omental sampling and biopsies in apparently free omentum. We are still waiting for the final results. Disclosure: Nothing to disclose.